The Roel of the Education Psychologists in the Formation of the Professional Direction of Adolescents - Varagushina N. A. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
the following article is devoted to one of the most pressing problems of educational psychology, the importance of the role of a education psychologists in the development of the professional orientation of teenagers. The article contains the names of well-known teachers and psychologists who study professional orientation. The essence of such concepts as «vocational guidance», «professional orientation» is revealed. The methods and forms of work of an education psychologists on career guidance, as well as psychological and pedagogic support of the process of forming a professional orientation are considered.
Keywords: профориентация; психолого-педагогическое сопровождение; направленность; подростковый возраст; professional orientation; vocational guidance; профессиональная направленность; adolescence; orientation; psychological and pedagogic support